GLOBALIZATION OF THE KOREAN EDUCATION SYSTEM AND PROMOTION OF KOREAN LANGUAGE IN UKRAINE (THE CASE OF PRYDNIPROVIA REGION) - Gi Yon (Vìsnik Unìversitetu ìmenì Alʹfreda Nobelâ: Serìâ Pedagogìka ì Psihologiâ, 2019)
The article investigates an impact of the globalization on higher education, in particular, South Korea and Ukraine cases. The purpose of the article is to identify the correlation between the main tasks of the globalization of the Korean education system and the promotion of the Korean language in Ukraine (the case of Prydniprovia region). A number of theoretical methods are used in the research, such as analysis, comparison and systematization of the content of psychological and pedagogical, literature, public and normative documents, structural and system analysis, through which the state of development of the problem of globalization of higher education was determined, the essence and characterization of the main tasks of the development of higher education in the Republic of Korea were given; generalization of theoretical regulations and their interpretation were conducted to substantiate the globalization of higher education as its features. Firstly, the state of the problem in each of the countries surveyed was described, and an overview of the main tasks of the Globalization of Korean Education System was presented, such as: Reinforcement of Multicultural Education; Support for Students Defected from North Korea; Expansion of Official Development Assistance in the Education Sector; Promotion of Student Exchange Programs and Outstanding International Students. It is found out that the globalization as a peculiarity of higher education in the era of the fourth industrial revolution creates conditions for the internationalization of higher education and requires (stimulates) the promotion of the Korean language in other countries in order to prepare both potential international students for Korean higher education institutions and potential future professionals for Korean business that is promoting in international markets. Then, for the first time a retrospective analysis of the Korean language promotion in Ukraine (the case of Prydniprovia region) was implemented and the essential stages were identified. The correlation between the main tasks of the globalization of the Korean education system and the promotion of the Korean language in Ukraine is revealed, which corresponds to the state of Ukrainian-Korean relations development. The author sees the prospects for further scientific research in the study of opportunities for a greater lability of the Ukrainian-Korean cooperation in the market of educational services under the rapidly changing requirements of the global competitive economic market.